Exact Soliton Solutions to the Cubic-Quartic Non-linear Schrodinger Equation With Conformable Derivative - Dutta, Hemen; Gunerhan, Hatira; Ali, Karmina K.; Yilmazer, Resat (Frontiers Media Sa, 2020)
The research paper aims to investigate the space-time fractional cubic-quartic non-linear Schrodinger equation in the appearance of the third, and fourth-order dispersion impacts without both group velocity dispersion, and disturbance with parabolic law media by utilizing the extended sinh-Gordon expansion method. This method is one of the strongest methods to find the exact solutions to the non-linear partial differential equations. In order to confirm the existing solutions, the constraint conditions are used. We successfully construct various exact solitary wave solutions to the governing equation, for example, singular, and dark-bright solutions. Moreover, the 2D, 3D, and contour surfaces of all obtained solutions are also plotted. The finding solutions have justified the efficiency of the proposed method.
Keywords: the non-linear cubic-quartic Schrodinger equation; conformable derivative; analytical solutions; the extended sinh-Gordon expansion method; solitary wave solutions